Trauma patients with tibia/fibula fractures are associated with an increased risk of torso, severe head, and severe spine injuries compared to patients with femur fractures. Issue 6 (June 2021) - Yu, Jingjing; Grigorian, Areg; Learned, James; Dolich, Matthew; Lekawa, Michael; Kuza, Catherine M.; Nahmias, Jeffry
Highlights: Trauma patients with tibia/fibula fractures are associated with increased risk of torso injuries compared to patients with femur fractures. Tibia/fibula fracture patients are associated with increased risk of severe head and severe spine injuries compared to femur fracture patients. Trauma surgeons should have high clinical suspicion of concomitant injuries in patients with tibia/fibula fractures. Abstract: Background: Although previous studies have demonstrated an association between lower extremity fractures and concomitant torso (thorax and abdomen) injuries in trauma patients, they do not compare different types of fractures. Therefore, we investigated the risk of associated torso injuries between femur and tibia/fibula fractures, hypothesizing that trauma patients with femur fractures are at higher risk of torso injuries compared to patients with tibia/fibula fractures. Methods: The Trauma Quality Improvement Program database (2010-2016) was queried for patients presenting with either femur or tibia/fibula fractures. Patients with ground-level falls and penetrating injuries were excluded. Univariable and multivariable logistic regression analyses were performed. Results: From 162, 354 patients, 104, 075 (64.1%) patients had femur fractures and 58, 279 (35.9%) had tibia/fibula fractures. Compared to those with femur fractures, patients with tibia/fibula fractures had a higher incidence of torso injuries (32.2% vs. 17.7%, p<0.001). The tibia/fibula fracture group was also associated with an increased risk of torso (OR 2.22, CI 2.17-2.27, p<0.001), severe (abbreviated injury scale grade > 3) head (OR 2.38, CI 2.30-2.46, p<0.001), and severe spine injuries (OR 2.33, CI 2.07-2.62, p<0.001) compared to the femur fracture group. Additionally, patients with tibia/fibula fractures had a higher rate of deep vein thrombosis (2.5% vs. 1.8%, p<0.001) than patients with femur fractures. Conclusions: Contrary to previous studies, we demonstrate patients with tibia/fibula fractures have a higher associated risk of torso, severe head and severe spine injuries than patients with femur fractures. Therefore, trauma surgeons should manage tibia/fibula fracture patients with similar clinical vigilance as femur fracture patients.